2016
DOI: 10.1080/2162402x.2016.1196310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical characterization of PD-L1 expression at transcriptional level via 976 samples of brain glioma

Abstract: Background: PD-L1 has been widely reported as immune check points in a range of malignancies as well as some immune-originated diseases. In glioma, the role of PD-L1 remains unclear. We aimed at investigating its role at transcriptome level and relationship with clinical practice.Method and patients: In total, 976 glioma samples with transcriptome data, including 301 microarray data from Chinese Glioma Genome Atlas (CGGA project) and 675 RNAseq data from TCGA project, were enrolled into our study. Clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
165
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(182 citation statements)
references
References 31 publications
14
165
0
1
Order By: Relevance
“…Similar to most immune checkpoints, B7‐H3 expression was significantly upregulated along with tumor grade, suggesting the dysregulation of immune response in higher‐grade gliomas. In molecular subtypes, we also discovered a similar expression pattern of B7‐H3 to PD‐L1, which was described in our previous study . Moreover, the ROC curve indicated that B7‐H3 can serve as a marker for mesenchymal subtype, reflecting the most profound inflammatory response in mesenchymal subtype tumors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to most immune checkpoints, B7‐H3 expression was significantly upregulated along with tumor grade, suggesting the dysregulation of immune response in higher‐grade gliomas. In molecular subtypes, we also discovered a similar expression pattern of B7‐H3 to PD‐L1, which was described in our previous study . Moreover, the ROC curve indicated that B7‐H3 can serve as a marker for mesenchymal subtype, reflecting the most profound inflammatory response in mesenchymal subtype tumors.…”
Section: Discussionsupporting
confidence: 84%
“…Accumulating evidence indicates that key components of immune response are significantly altered in gliomas, which subsequently leads to the evasion of immune surveillance of tumor cells . Immune checkpoints are thought to play a critical role in tumor immune escape . The dysregulation of immune checkpoints has attracted the attention of numerous scientific researchers and drug companies who have sought to develop inhibitors against these immune checkpoints in the tumor environment.…”
Section: Introductionmentioning
confidence: 99%
“…CD204 was positively correlated with the protein tyrosine kinases HCK and LCK and with MHC‐I, but negatively correlated with interferon and IgG in the CGGA (Figure A and ) and TCGA datasets (Figure A and B). Additionally, CD204 was highly correlated with the immune checkpoint regulators PD‐L1 and TIM‐3 in gliomas …”
Section: Resultsmentioning
confidence: 99%
“…To explore the biometric features of LUAD with lncRNAs in lncRNA signature, we identified the genes that highly related with these above lncRNAs (Pearson | R | > 0.5) in TCGA database …”
Section: Methodsmentioning
confidence: 99%